ON THE ISSUE OF BRINGING TO ADMINISTRATIVE RESPONSIBILITY FOR THE DISSEMINATION OF “FAKE” NEWS - PANTAZY JU.V. (Legal Bulletin)
The relevance of this article is determined by the problem of dissemination of false information under the guise of reliable information (so-called “fakes”). The main goal is to analyze the norms of the CAO RF on responsibility for “fakes”, law enforcement practice on these norms, review of foreign experience in combating “fakes”. The problems under consideration - the article studies the conditions that contributed to the growth of “fake” news, as well as the official reaction of the state to “fakes”, which was expressed in the amendment of the CAO RF and the application of the corresponding corpus delicti of administrative offenses. The methods used. The article uses general scientific methods of induction and deduction, analysis and synthesis. In addition to general scientific methods, special legal methods (comparativist, formallegal) were used.